Cardiac Troponin Release is Associated with Biomarkers of Inflammation and Ventricular Dilatation During Critical Illness. Issue 6 (June 2017) - Ostermann, Marlies; Ayis, Salma; Tuddenham, Emma; Lo, Jessica; Lei, Katie; Smith, John; Sanderson, Barnaby; Moran, Carl; Collinson, Paul; Peacock, Janet; Rhodes, Andrew; Treacher, David
ABSTRACT: Introduction: Troponin release is common during critical illness. We hypothesized that there was an association between cardiac troponin T (cTnT) and biomarkers of systemic inflammation and ventricular dilatation. Methods: In an observational prospective cohort study, we enrolled consecutive adult patients admitted for noncardiac reasons to the intensive care unit (ICU) in two tertiary care centers. We measured cTnT, C-reactive protein (CRP), interleukin-6 (IL-6), procalcitonin (PCT), and N-terminal pro brain natriuretic peptide (NT-proBNP) daily in the first week, and on alternate days in the second week. Using a peak cTnT cutoff ≥15 ng/L and concomitant changes on electrocardiogram, patients were categorized as "definite myocardial infarction (MI), " "possible MI, " "cTnT rise only, " or "no cTnT rise." Within each group, associations between CRP, IL-6, PCT, NT-proBNP, and cTnT were investigated using mixed effect models. Results: One hundred seventy-two patients were included in the analysis of whom 84% had a cTnT rise ≥15 ng/L. Twenty-one patients (12%) had a definite MI, 51 (30%) had a possible MI, and 73 (42%) had a cTnT rise only. At the time of peak cTnT, 71% of patients were septic and 67% were on vasopressors. Multivariable analysis showed a significant association between cTnT and IL-6 in all patients with a cTnT rise independent of age, gender, renal function, and cardiovascular risk factors. In patients without a definite MI, cTnT levels were significantly associated with PCT and NT-proBNP values. In patients without elevated cTnT levels, there was no associated NT-proBNP rise. Conclusions: In ICU patients admitted for non-cardiac reasons, serial cTnT levels were independently associated with markers of systemic inflammation and NT-proBNP.